2017
DOI: 10.3168/jds.2015-10220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single injection of cabergoline at dry off on udder characteristics in high-yielding dairy cows

Abstract: In recent years, relationships between high milk yield at dry off, higher prevalence for new intramammary infections, and stress were evaluated. Considering increasing milk yield, dry off methods need to be refined to ensure udder health and animal welfare, especially in high-yielding dairy cows. The present work evaluated the effect of a single cabergoline injection (Velactis, Ceva Santé Animale, Libourne, France) at dry off on udder pressure, milk leakage, and signs of udder pain after dry off. A total of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
3
26
0
1
Order By: Relevance
“…Thus, cabergoline seems to moderately amplify and accelerate the opening of tight junctions. This effect could be due to reduced milk secretion after cabergoline treatment as indicated by a reduced udder pressure and firmness as well as milk leakage previously reported (Bach et al, 2015;Bertulat et al, 2017). However, further studies have to be performed to confirm this hypothesis.…”
Section: Effects Of Cabergoline Treatment On Mammary Involutionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, cabergoline seems to moderately amplify and accelerate the opening of tight junctions. This effect could be due to reduced milk secretion after cabergoline treatment as indicated by a reduced udder pressure and firmness as well as milk leakage previously reported (Bach et al, 2015;Bertulat et al, 2017). However, further studies have to be performed to confirm this hypothesis.…”
Section: Effects Of Cabergoline Treatment On Mammary Involutionmentioning
confidence: 78%
“…However, cabergoline is a stronger dopamine agonist than either quinagolide or bromocriptine, and thus, cabergoline may more likely affect glucose transport in MEC than the other dopamine agonists. Because lactose is the main osmotic agent in the milk, the downregulation of SLC2A1 mRNA could be one of the factors responsible for less udder engorgement and milk leakage observed in cows treated with cabergoline (Bach et al, 2015;Bertulat et al, 2017).…”
Section: Effects Of Cabergoline Treatment On Mammary Involutionmentioning
confidence: 99%
“…Therefore, as a result of studies carried out considering CAB as a potential drying off molecule, it was concluded that the intramuscular injection of a single dose of 5.6 mg of CAB on the cows, which gives over 16 kg of milk in the transition to dry period, Cabergoline treatment positively influences dry period mammary health and reduces risk factors for animal welfare. 44 In similar studies, it was reported that the same dose of CAB facilitated the drying of the udder gland and udder gland involution, reduced prolactin release and leakage from the udder, and prolonged the resting time after the drying off. [41][42][43] Cabergoline treatment will be beneficial because it accelerates mammary involution and decreases milk secretion in the transition to dry period.…”
Section: Utilization Of Cabergoline In Drying Off the Dairy Cowsmentioning
confidence: 92%
“…42 In recent years, it has been reported that, as an alternative to conventional drying off methods, successful results have been obtained with a single CAB injection in transition to the drying off phase. [41][42][43]44 Cabergoline is a high-affinity ergot derivative for D2 dopamine receptors, whose dopaminergic effects cause the inhibition of prolactin secretion. Therefore, as a result of studies carried out considering CAB as a potential drying off molecule, it was concluded that the intramuscular injection of a single dose of 5.6 mg of CAB on the cows, which gives over 16 kg of milk in the transition to dry period, Cabergoline treatment positively influences dry period mammary health and reduces risk factors for animal welfare.…”
Section: Utilization Of Cabergoline In Drying Off the Dairy Cowsmentioning
confidence: 99%
“…Laktasyon sonu süt üretimi fazla (25-30 kg/gün) olan ineklerde aniden sütten kesme ile kuruya alındığında, memeden süt sızıntısı artarak keratin plak oluşumunun geciktiği (25), patojen girişinin kolaylaştığı ve meme içi lökositlerinin fonksiyonunun azalttığı tespit edilmiştir (26). Bununla birlikte KD'ye girişte 12.5 kg'dan fazla süt üretiminde, her 5 kg süt için doğumda yeni meme içi enfeksiyon insidansının %77'ye kadar arttığı tespit edilmiştir (19).…”
Section: Meme Sağlığı Açısından Uygun Kuruya Alma Yöntemleriunclassified